2008
DOI: 10.1016/j.jweia.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in wind speed forecasts for wind power prediction purposes using Kalman filtering

Abstract: This paper studies the application of Kalman filtering as a post-processing method in numerical predictions of wind speed. Two limited-area atmospheric models have been employed, with different options/capabilities of horizontal resolution, to provide wind speed forecasts. The application of Kalman filter to these data leads to the elimination of any possible systematic errors, even in the lower resolution cases, contributing further to the significant reduction of the required CPU time. The potential of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(187 citation statements)
references
References 9 publications
1
183
1
2
Order By: Relevance
“…Similarly, Liu et al (2012) showed that downscaling ratios of 7 : 1, 5 : 1, and 3 : 1 in an WRF model perform better than smaller ratios in terms of rainfall. Resolution jumps (from the forcing data to the external model grid) higher than 5 : 1 and up to 10 : 1 have been successfully employed in various numerical studies (e.g., Galanis et al, 2006;Louka et al, 2008;Katsafados et al, 2011;Stathopoulos et al, 2013). The selection of the above-mentioned data sets was made for homogenization purposes of initial and boundary conditions for all cases.…”
Section: Data Sources and Model Setupmentioning
confidence: 99%
“…Similarly, Liu et al (2012) showed that downscaling ratios of 7 : 1, 5 : 1, and 3 : 1 in an WRF model perform better than smaller ratios in terms of rainfall. Resolution jumps (from the forcing data to the external model grid) higher than 5 : 1 and up to 10 : 1 have been successfully employed in various numerical studies (e.g., Galanis et al, 2006;Louka et al, 2008;Katsafados et al, 2011;Stathopoulos et al, 2013). The selection of the above-mentioned data sets was made for homogenization purposes of initial and boundary conditions for all cases.…”
Section: Data Sources and Model Setupmentioning
confidence: 99%
“…Other machine learning techniques that are common for load prediction include Kalman filters [20], recurrent neural networks [49], hidden Markov models [11], parallel classifiers [5] and firefly colony algorithm [8].…”
Section: Other Machine Learning Techniquesmentioning
confidence: 99%
“…If the finite set { } . Assume the distribution of the data at the high-dimensional manifold is uniform, the corresponding intrinsic correlation dimension is defined by 2 1…”
Section: Intrinsic Dimensionality Estimationmentioning
confidence: 99%
“…The wind speed forecasting has significant impact for security and stability of the large-capacity wind speed connected to the grid. Most forecasting methods such as time series [1], Kalman filtering [2], Artificial neural networks (ANNs) [3], numerical weather prediction [4], fuzzy logic method [5] and support vector machine [6], don't take into account the distribution characteristics of meteorological data. The main disadvantages of the outlined literature include that: they do not provide a complex analysis for the model structure design and selection, such as the model variables selection, model variable order estimation as well as the performance measurement criteria, typically, there are plenty of available variables which can be used for modeling; however, the proper variables with approximately model order are not provided, which results in lacking the ability of generalization and practicability.…”
Section: Introductionmentioning
confidence: 99%